Fingerprinting of elite cytoplasmic male-sterile (CMS) lines of Pearl millet (Pennisetum glaucum (L.) R. Br.) using proteins and isozymes - Gulati, S.=700 1 Chhabra, A.K.; Behi, R.K.; Nijhawan, D.C.; Dhillon, S.
(En, Fr, Es)
Ilus., 15 ref.
Keywords: PENNISETUM GLAUCUM; HIBRIDACION; ESTERILIDAD MASCULINA CITOPLASMICA; PROTEINAS; ISOENZIMAS; ITALIA; MIJO PERLA